ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN KELAS IBU HAMIL DI PUSKESMAS SIMPANG KANAN KOTA SUBULUSSALAM PROVINSI ACEH - Marsaulina, Ivasri (Jurnal Maternitas Kebidanan, 2024)
According to WHO, more than 350,000 women worldwide die each year from complications of pregnancy and childbirth. IDHS data on the number of cases of maternal death during childbirth decreased from 4,999 cases in 2015 to 4,912 cases in 2016. Meanwhile, until the first semester of 2017 there were 1,712 cases of maternal death during childbirth. Efforts to accelerate the decline in MMR, the government has set many strategies and policies in the form of health improvement programs by conducting classes for pregnant women. The purpose of this research is to analyze factors that affect the implementation of classes for pregnant women in the Simpang Kiri Health Center Work Area, Subulussalam City, Aceh Province in 2020".The design of this research is analytic correlation using a cross sectional study. The total population is 37 respondents and the sample uses a total sampling of 37 pregnant women. The data used are primary and secondary data. Data analysis using univariate and bivariate using chi square test.The results obtained using the chi square test, the effect of knowledge on the implementation of the pregnant women class p = 0.033, there is the effect of distance to health facilities on the implementation of the pregnant women class p = 0.034, there is an effect of husband's support on the implementation of the pregnant women class p = 0.023, in the Simpang Kiri Health Center Work Area, Subulussalam City, Aceh Province in 2020. The conclusion is that there is an influence of knowledge, education, work, distance to health facilities, husband's support for the implementation of pregnant women classes in the Simpang Kiri health center work area Subulussalam City, Aceh Province in 2020. Expected to officers s health, especially midwives, to be more active in disseminating information about the class program for pregnant women, not only to pregnant women, but also to their husbands/partners and families. Keywords : Knowledge,Distance to Health Facilities, husband's support, Maternity Class